Targeting NUPR1 with the small compound ZZW-115 is an efficient strategy to treat hepatocellular carcinoma. (28th August 2020) - Lan, Wenjun; Santofimia-Castaño, Patricia; Xia, Yi; Zhou, Zhengwei; Huang, Can; Fraunhoffer, Nicolas; Barea, Dolores; Cervello, Melchiore; Giannitrapani, Lydia; Montalto, Giuseppe; Peng, Ling; Iovanna, Juan
Abstract: HCC is a highly lethal malignancy with Sorafenib as the only molecularly targeted drug. The multifunctional stress-associated protein, NUPR1, plays an essential role in controlling cell growth, migration, invasion and Sorafenib resistance in HCC. We report here that NUPR1 expression is absent in healthy liver and it is progressively upregulated in HCC premalignant lesions such as hepatitis and cirrhosis with a maximum expression in HCC samples, highlighting that NUPR1 is a potential drug target for HCC. We therefore assessed in this work, ZZW-115, a strong inhibitor of NUPR1, as a promising candidate for the treatment of HCC. We validated its extraordinary antitumor effect on HCC by using two HCC cell lines, HepG2-and Hep3B, both in cell based experiments and xenografted mice. We further revealed that ZZW-115 treatment induced cell death by apoptosis and necroptosis mechanisms, with a concomitant mitochondrial metabolism failure that triggers lower ATP production. Furthermore, the ATP depletion cannot be rescued by the apoptosis inhibitor Z-VAD-FMK and/or the necrosis inhibitor Necrostatin-1, indicating that ZZW-115 induces cell death through the mitochondrial failure. Highlights: There is an urgent demand of novel and efficacious therapeutics for treating HCC. NUPR1 plays an essential role in controlling cell growth, migration, invasion and Sorafenib resistance in HCC. NUPR1 expression is absent in healthy liver and it is progressively upregulated in HCC premalignant lesions such as hepatitis and cirrhosis with a maximum expression in HCC samples. ZZW-115 is a strong inhibitor of NUPR1 and therefore a promising candidate for the treatment of HCC. We demonstrated the extraordinary antitumor effect of ZZW-115 on HCC by using two HCC cell lines, both in cell-based experiments and xenografted mice. ZZW-115 treatment induced cell death by apoptosis and necroptosis mechanisms, with a concomitant mitochondrial metabolism failure that triggers lower ATP production.